If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -9 = 5y + 40 Reorder the terms: -9 + -2y = 5y + 40 Reorder the terms: -9 + -2y = 40 + 5y Solving -9 + -2y = 40 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -9 + -2y + -5y = 40 + 5y + -5y Combine like terms: -2y + -5y = -7y -9 + -7y = 40 + 5y + -5y Combine like terms: 5y + -5y = 0 -9 + -7y = 40 + 0 -9 + -7y = 40 Add '9' to each side of the equation. -9 + 9 + -7y = 40 + 9 Combine like terms: -9 + 9 = 0 0 + -7y = 40 + 9 -7y = 40 + 9 Combine like terms: 40 + 9 = 49 -7y = 49 Divide each side by '-7'. y = -7 Simplifying y = -7
| -6a^3+5a+2a^3+4a^3= | | 5(-5+x)=6x-1/5 | | 63=3+6n | | 3+6b=5b-4 | | w-4/w-5=w-5/w-3+1 | | 6y-1=3y+5 | | 32=-8b | | 6=3+6n | | 3(v+9)=5v+31 | | -9+18-8=f | | 11/2y+21/6=5y-5 | | n+1=-2n-8 | | f=-36+12(6)+-35 | | f=36+12(6)-35 | | 3(7x-3)=22x | | 6(1/3s+4)=20 | | q=3m+3w | | 15=a/3+6 | | 5/x=10/18 | | -4c+3=-1 | | 4*15+3*-0.75=60 | | -7s^2-4s^2= | | 8b-6=7b-8 | | 14x-12=3(4x-3)+2x-3 | | (2(x/(x+4))^2)-(5(x/(x+4)))-3=0 | | 0.01(5x+4)=0.04-0.01(x+3) | | 45-3x=-6s | | 6(3x-2)-5(2x-7)=79 | | 30-15=3(x-1) | | 3*3=9 | | 34+3y-9=13y-10-5y | | 5w=1633 |